The Boom's Near Future. - O'Connell, Hugh Charles (CR: The New Centennial Review)
The article presents literary criticism of the book "The Execution Channel" by Ken MacLeod and the "Bold as Love" series of novels by Gwyneth Jones, including the books "Castles Made of Sand" and "Midnight Lamp". It explores the roles of magic and utopian possibility in British science-fiction portrayals of the near future as of 2013. Topics discussed include late capitalism, imagination, and crisis.